Economic relations between Latin America and the Caribbean and the Republic of Korea : advances and opportunities (United Nations SantiagoCL, 2015)
Examines the economic relations between Latin America and the Caribbean and the Republic of Korea. Highlights opportunities for the diversification of bilteral trade in the coming years.
Keywords: ECONOMIC RELATIONS